Penicillin resistance and antimicrobial susceptibilities of coagulase positive staphylococci isolated from bovine mastitic milk samples - Uçkun Sait Uçan; Emine Asian (Eurasian Journal of Veterinary Sciences)
Coagulase activity, Bet a-lactamase production and antibiotic susceptibility of the Staphylococcus strains isolated Irom mastitic udders of cows from Konya District were evaluated in this study. Seventy five (92.6 %) S.aureus and 6 strains (7.4%) S.intermedius were identified. Of S.aureus strains, 49 (65.3%) were lound to be (i-!aktamase positive. The corresponding value for the S.intermedius was 2 (33.3%). Eight (10,6%) ol the Saureus and 4 (66.7%) of the S.intermedius strains were observed to be susceptible to all antibiotics tested. One of the S.aureus strains was observed to have resistance to meticillin. All ol the strains (100%) showed susceptibility to Danofloxacin. Degrees of the antibiotic susceptibility by the strains as follows: ampicillin+sulbactam and meticillin (98.8% each) oxacillin and amoxicillin+clavulanic acid (97.5% each), cloxacillin (96.3%). amoxicillin (22.2%) ve penicillin G (14.8%).